2019
DOI: 10.3390/app9224773
|View full text |Cite
|
Sign up to set email alerts
|

Polyisobutylene-Based Thermoplastic Elastomers for Manufacturing Polymeric Heart Valve Leaflets: In Vitro and In Vivo Results

Abstract: Superior polymers represent a promising alternative to mechanical and biological materials commonly used for manufacturing artificial heart valves. The study is aimed at assessing poly(styrene-block-isobutylene-block-styrene) (SIBS) properties and comparing them with polytetrafluoroethylene (Gore-texTM, a reference sample). Surface topography of both materials was evaluated with scanning electron microscopy and atomic force microscopy. The mechanical properties were measured under uniaxial tension. The water c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 61 publications
1
26
0
Order By: Relevance
“…In a previous work [8], we have demonstrated that for the synthesis of triblock copolymer of isobutylene and styrene (SIBS, M n = 33,000 g mol −1 , Ð = 1.30) in open conditions (without using of glovebox), the slightly higher concentrations of TiCl 4 (59 mM vs. 40 mM [20]) and proton trap (5.8 mM vs. 3.8 mM) need to be used for providing comparable reaction rate and crossover efficiency during block copolymer preparation. This could be explained by a much higher amount of adventitious H 2 O in the system when the preparation of block copolymer is performed in open conditions as compared to the glovebox technique.…”
Section: Effect Of Proton Trap Nature and Initiator Concentrationmentioning
confidence: 90%
See 1 more Smart Citation
“…In a previous work [8], we have demonstrated that for the synthesis of triblock copolymer of isobutylene and styrene (SIBS, M n = 33,000 g mol −1 , Ð = 1.30) in open conditions (without using of glovebox), the slightly higher concentrations of TiCl 4 (59 mM vs. 40 mM [20]) and proton trap (5.8 mM vs. 3.8 mM) need to be used for providing comparable reaction rate and crossover efficiency during block copolymer preparation. This could be explained by a much higher amount of adventitious H 2 O in the system when the preparation of block copolymer is performed in open conditions as compared to the glovebox technique.…”
Section: Effect Of Proton Trap Nature and Initiator Concentrationmentioning
confidence: 90%
“…Besides good mechanical properties, SIBS also has the advantage of a completely saturated polyisobutylene mid-block that yields superior thermal, oxidative stability, and gas barrier properties [1][2][3][4]. Moreover, SIBS is biostable as well as bio-and hemocompatible that makes it perfect candidate for medical applications [3,[5][6][7][8]. Particularly, SIBS was used as coatings on metallic stents [5,7], carrier for a drug-eluting coronary stents [5,7], ophthalmic implants [5][6][7], artificial vascular graft [6,9], etc.…”
Section: Introductionmentioning
confidence: 99%
“…The polymerization was conducted under inert argon according to [ 17 ]. Then, 38.6 mg dicumyl chloride (initiator, 0.167 mmol) was dissolved in 107 mL methylcyclohexane/methylene chloride mixture (3:2) followed by the addition of 0.161 mL (1.39 mmol) 2,6-dimethylpyridin.…”
Section: Methodsmentioning
confidence: 99%
“…Here, we synthesized poly(styrene- block -isobutylene- block -styrene) (SIBS), a biomaterial demonstrating high biocompatibility [ 16 ] yet limited tensile strength [ 17 ], to further modify its structure with CNTs at different concentrations. The resulting nanocomposite films were subjected to a uniaxial tension test followed by analyses of hydrophobicity, electric conductivity, and cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…In 1997, Coca and Matyjaszewski reported block copolymers preparation of styrene (St) and IB, i.e., P(St-b-IB-b-St) ( P1 ) by combination of cationic and ATRP, where both St and IB monomers are capable of undergoing polymerization by living cationic techniques. A recent study proves P(St-b-IB-b-St) ( P1 ) is highly hemocompatible and can be used as heart valve leaflets in near future ( Table 1 ) ( Ovcharenko et al, 2019 ). Researchers have also studied surface mobility of heparin by synthesizing functional dendritic PIB-based thermoplastic elastomer by styrene (St) and IB copolymer ( Wu et al, 2018 ).…”
Section: Combination Of Living Cationic Polymerization With Other Polymerization Techniquesmentioning
confidence: 99%